Effects of fungal supplementation on endurance, immune function, and hematological profiles in adult athletes: a systematic review and meta-analysis - Shu, Meng-Yuan; Zhang, Xiu-Chang; Zuo, Li; Jiang, Fang-Lin; Liang, Jian; Li, Fang (Frontiers in Nutrition, 2025)
Edible fungi are rich in a wide array of bioactive compounds, and a growing body of evidence suggests that they possess anti-inflammatory, antioxidant, antitumor, anti-aging, and other beneficial properties. Although an increasing number of studies have investigated the potential benefits of fungal supplements for athletes, there is still a lack of comprehensive reviews that systematically synthesize the available evidence. We conducted a systematic literature search using the PubMed, Scopus, Web of Science, and CNKI databases. The search employed a combination of keywords, including mushroom, Cordyceps, Ophiocordyceps sinensis, Lion’s Mane mushroom, etc. and athlete. Fourteen randomized controlled trials involving 528 athletes were included, of which eight studies (n = 288) met the criteria for quantitative synthesis. Meta-analysis showed that Cordyceps sinensis supplementation significantly improved endurance performance (p = 0.05), ventilatory threshold (p = 0.03), and VO2peak (p = 0.04), indicating enhanced aerobic capacity with low heterogeneity. In contrast, Ganoderma lucidum supplementation resulted in significant reductions in blood urea nitrogen (p < 0.00001) and blood lactate (p < 0.00001), along with increases in hematocrit (p < 0.00001) and superoxide dismutase activity (p = 0.01). Subgroup analyses further revealed that both triterpenoid and polysaccharide extracts of G. lucidum significantly elevated hemoglobin concentrations (p < 0.00001), with stronger effects observed in endurance athletes. Our findings support the potential of fungal supplements as natural, safe, and effective ergogenic aids that enhance endurance, recovery, and physiological resilience in athletes.